Analysis of the Impact of Profitability and Liquidity on Stock Prices with Dividend Policy as an Intervening Variable (A Case Study of Companies in the Food and Beverage Sector) - Salsabillah, Nadia; Rahmawati, Imelda Dian; Supardi, Supardi (Amkop Management Accounting Review (AMAR), 2025)
The present study aims to analyse how profitability and liquidity influence stock prices, with dividend policy serving as an intervening variable, within the food and beverage sector. The research population comprises 96 food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. A purposive sampling technique was employed to select 25 companies based on specific predetermined criteria. The present study is supported by secondary data sourced from companies' financial statements and annual reports, which were accessed through the official Indonesia Stock Exchange website (www.idx.co.id). The analysis of the data was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method, with statistical processing performed in SmartPLS version 4.1. The findings indicate that profitability exerts a substantial influence on dividend policy, whereas liquidity is inconsequential. Furthermore, profitability exerts a substantial influence on stock prices, whereas liquidity shows no statistically significant impact. The study's findings demonstrate that dividend policy does not exert a substantial influence on stock prices and does not serve as an intermediary in the relationship between profitability and liquidity.